meningkatkan keterampilan observasi, merencanakan percobaan, dan berkomunikasi berdasarkan pendekatan STEM - Yuni Syahraini; Muhammad Syukri; Evendi; Elisa Kasli; Nurazidawati Mohamad Arsad; Elva Sesioria Putri (Postgraduate, University of Mataram, 2024)
Physics learning needs to emphasize science process skills (KPS) in students. In fact, from the results of a case study conducted at SMAN 2 Banda Aceh, it was found that the LKPD used by teachers was still conventional and there were no aspects of KPS. The purpose of this study was to determine the results of the application of physics LKPD based on the STEM approach in improving the KPS of high school students. This study used a quantitative approach of experimental type Non-Equivalent Control Group Design. The samples used in this study were X4 and X6 class students totaling seventy people taken by purposive sampling. The instrument in this study was the KPS test. Data analysis of this study used the average test, N-gain test and t-test. The results showed the average value of the experimental class KPS N-gain of 0.70 was in the high category and the control class N-gain of 0.63 was in the medium category. Based on the results of the t-test, it can be concluded that there are differences in the improvement of students' KPS in physics learning taught with the STEM approach and those taught using the direct learning model.